Central pontine myelinolysis in anorexia nervosa: case report of a Chinese adolescent - Gaohan Yin; Tianhang Zhou; Qingmei Kong (Journal of Eating Disorders)
Abstract Central pontine myelinolysis (CPM) is a rare neurologic disorder characterized by symmetric demyelination in the central region of pons. Until recently its prognosis was considered poor if not fatal. CPM may manifest as a severe complication of eating disorders, especially anorexia nervosa (AN), primarily due to a rapid correction of hyponatremia. In this report, we presented the case of a 13-year-old girl with a five-month history of AN who exhibited typical CPM brain lesions, confirmed by magnetic resonance imaging (MRI) examination without the context of severe electrolyte imbalances. Surprisingly, despite the patient’s critical clinical manifestations in the initial stages, her prognoses of both AN and CPM were relatively optimistic. We discussed these observations in the light of recent reports on CPM and AN comorbidity. Although the clinical implications of MRI-detected lesions remain uncertain, psychiatrists should be cautious about CPM when refeeding patients with AN. Further studies about the relationship between CPM and AN are imperative.